Demographic, clinical, laboratory and treatment characteristics of spondyloarthritis patients with and without acute anterior uveitis - Gehlen, Marcelo (2012)
CONTEXT AND OBJECTIVE: Acute anterior uveitis is a common extra-articular manifestation in spondyloarthritis patients. The aim of this study was to compare demographic, clinical, laboratory and treatment data among spondyloarthritis patients with and without acute anterior uveitis. DESIGN AND SETTING: This was a cross-sectional analytical study at the Rheumatology Outpatient Clinic of the Evangelical University Hospital, Curitiba, Brazil. METHODS: Spondyloarthritis patients with without acute anterior uveitis were compared regarding demographic data, spondyloarthritis subtype, peripheral arthritis, enthesitis, disease activity, functional index, physical examination, radiological involvement, HLA-B27 and treatment. RESULTS: Presence of acute anterior uveitis was not found to have any relationship with functional index, degree of radiological involvement, peripheral arthritis or enthesitis. Acute anterior uveitis showed a negative association with skin manifestations (P = 0.04) and a trend towards higher disease activity (P = 0.06). CONCLUSION: In the study sample, it could not be shown that AAU had any association with the functional and radiological prognoses. The patients with spondyloarthritis with and without acute anterior uveitis did not differ clinically except for a higher proportion of ankylosing spondylitis and smaller presence of skin involvement in those with uveitis.